Implantable Drug Reservoir Devices for Inner Ear Delivery of Pharmacotherapeutics. (2nd June 2020) - Kita, Ashley; Saldate, Johnny; Chang, Courtney; Chellappa, Nitika; Jong, Jeremy; Matsuda, Riley; Schmidt, Andrew; Shih, Brandon; Shafqat, Iram; Schoettler, Kari; Acharya, Shiv; Seidlits, Stephanie; et al.
Abstract : Objective: Cisplatin is a platinum‐based chemotherapeutic drug that secondarily induces toxicity in inner ear sensory epithelia, contributing to auditory and vestibular dysfunction. We describe the creation of a drug reservoir device (DRD) to combat this ototoxicity for the duration of chemotherapy. As ototoxic side effects of chemotherapy may limit an oncologist's ability to prescribe first‐line agents such as cisplatin, mitigating such devastating effects through prolonged topical therapy would be tremendously valuable. Study Design: We investigated (1) the ability of an electrospun polylactic acid DRD to provide prolonged delivery of the posited otoprotectant metformin and (2) the development of an in vitro model utilizing Sh‐Sy5y human neuroblastoma cells to assess the efficacy of metformin in reducing cisplatin‐induced toxicity. Setting: Neurophysiology laboratory. Methods: Basic science experiments were performed to assess DRD properties and metformin's effects on cisplatin toxicity in culture. Results: We found that DRDs with increasing polylactic acid concentrations exhibited metformin release for up to 8 weeks. In modeling elution across the round window in vitro, continued elution of metformin was observed for at least 6 weeks, as quantified by spectrophotometry. Unfortunately, metformin did not exhibit protective efficacy in this model using Sh‐Sy5y cells. Conclusion: While metformin was not found to be protective in Sh‐Sy5y cells, these results suggest that an electrospun DRD can provide a tailorable drug delivery system providing medication for the duration of chemotherapy treatment. This represents a novel drug delivery system and efficacy screening assay with broad clinical applications in personalized delivery of inner ear therapies.